2012
DOI: 10.1371/journal.pone.0038803
|View full text |Cite
|
Sign up to set email alerts
|

Localized Brain Activation Related to the Strength of Auditory Learning in a Parrot

Abstract: Parrots and songbirds learn their vocalizations from a conspecific tutor, much like human infants acquire spoken language. Parrots can learn human words and it has been suggested that they can use them to communicate with humans. The caudomedial pallium in the parrot brain is homologous with that of songbirds, and analogous to the human auditory association cortex, involved in speech processing. Here we investigated neuronal activation, measured as expression of the protein product of the immediate early gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…For example, immediate-early gene (IEG) auditory responses (i.e. ZENK induction in NCM in response to auditory playbacks) yield varying results depending on species: no differences between NCM subregions are reported in in adult male European starlings 81 or adult male budgerigars 82 , whereas higher dNCM ZENK compared to vNCM has been reported in both adult female white-crowned sparrows 83 and both sexes of adult black-capped chickadees 84, but see 85 . In contrast, extracellular recordings in the NCM of adult starlings find stronger experience-dependent changes in firing rates in ventral vs dorsal NCM 86 , which were suggested to be attributed to a noted enhanced thalamic input from Field L to ventral NCM (Vates et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…For example, immediate-early gene (IEG) auditory responses (i.e. ZENK induction in NCM in response to auditory playbacks) yield varying results depending on species: no differences between NCM subregions are reported in in adult male European starlings 81 or adult male budgerigars 82 , whereas higher dNCM ZENK compared to vNCM has been reported in both adult female white-crowned sparrows 83 and both sexes of adult black-capped chickadees 84, but see 85 . In contrast, extracellular recordings in the NCM of adult starlings find stronger experience-dependent changes in firing rates in ventral vs dorsal NCM 86 , which were suggested to be attributed to a noted enhanced thalamic input from Field L to ventral NCM (Vates et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, neuronal activation in the caudomedial pallium of the experimental birds correlated significantly and positively with the percentage of correct responses in the discrimination task. These results suggest that in a parrot, the NCM and the CMM are involved in auditory learning and memory, as they are in songbirds (Eda-Fujiwara et al, 2012).…”
Section: The Caudomedial Pallium and Tutor Song Memory: The Ncmmentioning
confidence: 68%
“…Eda-Fujiwara et al (2012) investigated the neural mechanisms of auditory discrimination learning in the budgerigar (Melopsittacus undulatus), a parrot. Like other parrots, budgerigars can learn to produce human words.…”
Section: The Caudomedial Pallium and Tutor Song Memory: The Ncmmentioning
confidence: 99%
“…For example, immediate-early gene (IEG) auditory responses (i.e. ZENK induction in NCM in response to auditory playbacks) yield varying results depending on species: no differences between NCM subregions are reported in in adult male European starlings (Gentner et al, 2004) or adult male budgerigars (Eda-Fujiwara et al, 2012), whereas higher dNCM ZENK compared to vNCM has been reported in both adult female white-crowned sparrows (Sanford et al, 2010) and both sexes of adult black-capped chickadees (Phillmore et al, 2003; but see Avey et al, 2014). In contrast, extracellular recordings in the NCM of adult starlings find stronger experience-dependent changes in firing rates in ventral vs dorsal NCM (Thompson and Gentner, 2010), which were suggested to be attributed to a noted enhanced thalamic input from Field L to ventral NCM (Vates et al 1996).…”
Section: Developmental and Regional Shifts In Neuronal Cell Density Imentioning
confidence: 99%